Формула функції Вейля через резольвенту оператора - Ivasyk, H. V.; Національний університет «Львівська політехніка», Львів; Kuchma, M. I.; Національний університет «Львівська політехніка», Львів (Pidstryhach Institute for Applied Problems of Mechanics and Mathematics of NAS of Ukraine, 2021)
The Weyl function for the Friedrichs model is determined by using the so-called branching of the resolvent. The formulae for the Weyl function via resolvent of operator is obtained. Sufficient conditions for the existence of the resolvent are given. Cite as: Ivasyk H. V., Kuchma M. I., “Formulae of Weyl function via resolvent of the operator,” Prykl. Probl. Mekh. Mat., Issue 19, 94–106 (2021) (in Ukrainian), https://doi.org/10.15407/apmm2021.19.94-106